(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the role of the education system of Kyrgyzstan in the transmission of national and religious values. The article examines the role of science in the preservation and development of national values in Kyrgyzstan. The significance of national values, their place in public life, the achievements of scientific research in this area and future problems are analyzed. The article pays attention to the works of Kyrgyz scientists on the study of national values, and also emphasizes the importance of the education system in this process.